Genetic diversity, population structure and kinship relationships highlight the environmental influence on Uganda’s indigenous goat populations - Nantongo, Ziwena; Birungi, Josephine; Opiyo, Stephen Obol; Shirima, Gabriel; Mugerwa, Swidiq; Mutai, Collins; Kyalo, Martina; Munishi, Linus; Agaba, Morris; Mrode, Raphael (Frontiers in Genetics, 2024)
Knowledge about genetic diversity and population structure among goat populations is essential for understanding of environmental adaptation and fostering efficient utilization, development, and conservation of goat breeds. Uganda's indigenous goats exist in three phenotypic groups as Mubende, Kigezi, and Small East African. However, limited understanding of their genetic attributes and population structure hinders the goats' development and sustainable utilization.Using the Goat Illumina 60k chip IGGC V2, whole genome data for 1021 indigenous goats sourced from ten agroecological zones in Uganda were analyzed for genetic diversity and population structure. A total of 49337 (82.6%) single nucleotide polymorphism (SNP) markers were aligned to the ARS-1 goat genome and used to assess genetic diversity, population structure and kinship relationships of Uganda's indigenous goats. Moderate genetic diversity was observed; the observed and expected heterozygosity were 0.378, and 0.383, average genetic distance was 0.390 while average minor allele frequency was 0.30. Average inbreeding co-efficient (Fis) was 0.014, and average fixation index (Fst) was 0.016. Principal component analysis, admixture analysis and discriminant analysis of principal components grouped the 1021 goat genotypes into three genetically distinct populations that did not conform to the known phenotypic populations but rather varying across environmental conditions. Population 1, comprising Mubende (90%) and Kigezi (8.1%) goats, is located in southwestern to central Uganda, a warm and humid environment.Population 2 which is 59% Mubende and 49% small East African goats is located along the river Nile delta in northwestern Uganda and around the Albertine region, a hot and humid savannah grassland. Population 3, comprising 78.4% Small East African and 21.1% Mubende goats is found in northeastern to eastern Uganda, a hot and dry cammiphora woodlands. Genetic diversity and population structure information from this study will be a basis for future development, conservation and sustainable utilization of Uganda's goat genetic resources.